Kesiapsiagaan Mahasiswa Keperawatan Universitas Advent Indonesia dalam Penanggulangan Bencana - Tulungen, Angelica Andriani; Rantung, Gilny Aileen Joan (NUTRIX, 2024)
Nursing students' preparedness to respond to disasters is a key element in disaster management. This study aims to evaluate the disaster preparedness perception among nursing students at Advent Indonesia University in disaster management. Employing a descriptive quantitative design, this research utilized the Disaster Preparedness Evaluation Tool (DPET) section on Disaster Preparedness Perception. The respondents consisted of 101 nursing students from Advent Indonesia University, selected using convenience sampling technique. The study's findings indicate that the disaster preparedness perception level is in the moderate category, with an average score of 3.65. Students displayed high interest in disaster preparedness education but had limited access to practical resources and information. In terms of preparedness skills, students showed a good understanding of triage principles in disaster situations but lacked confidence in taking on leadership roles during disasters. Family preparedness for disasters revealed that most students had taken proactive steps, indicating effective communication and planning among family members. There is a need to develop the disaster education curriculum in nursing with practical elements such as disaster simulations and structured leadership training. This aims to enhance awareness and readiness among students in facing disasters. Further research is recommended to evaluate training modules that align with the context of disaster preparedness. Nursing students at Universitas Advent Indonesia generally have a moderate level of perceived disaster preparedness. This indicates that while students have demonstrated awareness and understanding of disaster preparedness through training and education, there is still a need to improve the practical aspects and application of this knowledge in real situations. Kesiapsiagaan mahasiswa keperawatan untuk merespons bencana adalah elemen kunci dalam penanggulangan bencana. Penelitian ini bertujuan untuk mengevaluasi persepsi kesiapsiagaan mahasiswa keperawatan di Universitas Advent Indonesia dalam penanggulangan bencana. Penelitian ini menggunakan desain deskriptif kuantitatif dengan menggunakan kuesioner Disaster Preparedness Evaluation Tool (DPET) bagian Persepsi Kesiapsiagaan Bencana. Responden berjumlah 101 mahasiswa keperawatan Universitas Advent Indonesia yang dipiilih dengan menggunakan teknik convenience sampling. Hasil penelitian menunjukan bahwa tingkat persepsi kesiapsiagaan bencana berada pada kategori sedang dengan nilai rata-rata sebesar 3,65. Mahasiswa menunjukkan ketertarikan yang tinggi terhadap pendidikan kesiapsiagaan bencana, namun memiliki akses terbatas ke sumber daya dan informasi praktis. Dalam hal keterampilan kesiapsiagaan, mahasiswa menunjukkan pemahaman yang baik tentang prinsip-prinsip triase dalam situasi bencana, tetapi kurang percaya diri dalam mengambil peran kepemimpinan saat bencana. Persiapan keluarga untuk bencana menunjukkan bahwa sebagian besar mahasiswa telah mengambil langkah proaktif, dengan indikasi adanya komunikasi dan perencanaan yang efektif antar anggota keluarga. Kurikulum pembelajaran bencana pada keperawatan perlu dikembangkan dengan elemen praktis seperti simulasi bencana dan pelatihan kepemimpinan. Hal ini bertujuan untuk meningkatkan kesadaran dan kesiapan mahasiswa dalam menghadapi bencana. Disarankan penelitian lanjutan untuk mengevaluasi modul pelatihan yang sesuai dengan konteks kesiapsiagaan bencana.